From Low Participation to High Engagement: Developing Extracurricular Programs to Optimize Students’ Talents and Interests - Sumardi, Sumardi; Muhaemin, Muhaemin; Ilham, Dodi (International Journal of Asian Education, 2025)
This study aimed to develop extracurricular program guidelines to increase student participation and optimize talent and interest development in a rural Indonesian senior high school. Using a Research and Development (R&D) approach with the 4D model—Define, Design, Develop, Disseminate—the research involved 102 students, 10 extracurricular coaches, eight subject teachers, and the school principal at SMAN 11 Luwu Timur. Data were gathered through questionnaires, interviews, observations, and document reviews, with subsequent expert validation and practicality testing. Needs analysis revealed limited facilities, misalignment between programs and student interests, scheduling conflicts, and low parental support as the main barriers to participation. The guidelines addressed these challenges through clearly defined objectives, flexible scheduling, diverse and technology-based activities, and strategies for resource management and community involvement. Expert validation produced a high validity score of 76.88%, while practicality testing averaged 76.15%, indicating that the guidelines were easy to implement and adaptable to various activities. The framework aligns with the Pancasila Student Profile, Gardner’s Multiple Intelligences Theory, and Self-Determination Theory, ensuring both theoretical robustness and contextual relevance. These findings suggest that well-designed, resource-efficient extracurricular programs can enhance student engagement even in resource-limited contexts. The guidelines offer a practical, scalable model for other schools with similar challenges, contributing to the promotion of equitable access to holistic education in rural settings.